Effect of Micronutrient Application on Seed Yield and Quality of Coriander - CA BABARIYA; JB PATEL; JYOTI SONDARVA; DV SAVALIYA (Seed Research, 2026)
Pure seeds of coriander cv. Gujarat Coriander-2 which formed the base material for the study were obtained from Department of Seed Science and Technology, College of Agriculture, JAU, Junagadh. The field experiment comprising 17 treatmentswas conducted at the Sagdividi farm, DSST, JAU, Junagadh for three seasons (Rabi 2016-17, 2017-18 and 2018-19) using Randomized Block Design (Factorial) with two factors, factor one was soil application and factor second was foliar application and one absolute control. The results revealed that on pooled basis, among the soil application treatments of micronutrients, significantly the higher seed yield (2099.75 kg/ha) was recorded in soil application of FeSO4 @ 25 kg/ha + RDF over CuSO4 @ 25 kg/ha + RDF (1895.58 kg/ha), MnSo4 @ 25 kg/ha + RDF (1888.32 kg/ha) and control (1592.96 kg/ha), and amongst the foliar application treatments, foliar application of FeSO4 @ 0.5% + 0.1% Citric Acid at 30 & 45 DAS + RDF recorded significantly the higher seed yield (2143.29 kg/ha) over CuSO4 @ 0.5% + 0.25% Calcium Carbonate at 30 & 45 DAS + RDF (1863.68 kg/ha), MnSo4 @ 0.5% + 0.25% Calcium Carbonate at 30 & 45 DAS + RDF) (1813.77 kg/ha) and control (1592.96 kg/ha). On mean basis, the treatment combination of soil application of FeSO4 @ 25 kg/ha + RDF and foliar application of FeSO4 @ 0.5% + 0.1% Citric Acid at 30 & 45 DAS + RDF recorded the high means for seed yield, yield attributes and quality parameters. The highest gross return (280853 `/ha), net return (221849/ha) as well as benefit cost ratio (BCR) (3.76) was obtained from the seed harvested from treatment combination of soil application of FeSO4 @ 25 kg/ha + RDF and foliar application of FeSO4 @ 0.5% + 0.1% Citric Acid at 30 & 45 DAS + RDF.